Effects of inflation expectations on macroeconomic dynamics: Extrapolative versus regressive expectations - Marji Lines; Frank Westerhoff (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2009)
In this paper we integrate heterogeneous inflation expectations into a simple monetary model. Guided by empirical evidence we assume that boundedly rational agents, selecting between extrapolative and regressive forecasting rules to predict the future inflation rate, prefer rules that have produced low prediction errors in the past. We show that integrating this behavioral expectation formation process into the monetary model leads to the possibility of endogenous macroeconomic dynamics. For instance, our model replicates certain empirical regularities such as irregular growth cycles or inflation persistence. Moreover, we observe multi-stability via a Chenciner bifurcation.
Keywords: C62; C63; E31; E32; 330; Extrapolative and regressive expectations; dynamic predictor selection; macroeconomic dynamics; nonlinearities and chaos; bifurcation analysis; Inflationserwartung; Geldtheorie; Makroökonomik; Dynamisches Modell; Chaostheorie; Theorie